Manipulation of sports competitions in the Lithuanian football: empirical research - Zaksaitė, Salomėja (Kriminologijos studijos, 2024)
This article deals with the topic of manipulation of sports competitions. It discusses the results of a unique empirical research, which gathered data from experts with a wealth of first-hand knowledge. Due to the specificity of such a study, the vast majority of the data is anonymised and/or pseudonymised. Nevertheless, the research is as natural as possible, especially due to the the sensitivity of the topic and jargon. The study revealed that manipulation is a serious problem in Lithuanian football, although the peak of this phenomenon is probably in the past. The research revealed intriguing connections that show that manipulation is far from being only a sports issue. It is a phenomenon closely linked to other scourges of the sporting community and society as a whole: the disregard for good governance, the lack of transparency and publicity, and the role of organised crime in the world of sport. Although the study did not specifically test criminological theories, the findings gathered from the research confirmed the insights of the strain and differential association theories. One of the ways in which manipulation is carried out clearly corresponds to the pattern drawn in the context of the two theories: starting with simple betting, players become addicted and indebted, and consequently feel constant tension, and only later, through a gradual interaction, does one start to talk about the manipulation of sporting competitions. It is also important to note that the betting market is precisely the environment where players can satisfy their need for competitiveness and release excessive adrenaline. Perhaps for this reason, football players who play in lower leagues or whose careers are ending – that is, who are no longer able to succeed and let off steam on the field – are frequently caught by the betting hook. This creates an addiction to betting, potentially leading to committing fraud. From a legal perspective, the problem of manipulation of sports competitions can be explained by the difficulties in the application of the Criminal Code of the Republic of Lithuania: in the context of an unclear concept of professional sport, it is not obvious which competitions meet or do not meet the criterion of professionalism (which, up to now, has been required for the incrimination of manipulation of sports competitions).
Keywords: manipulations of sports competitions; empirical research; betting market; problems in the application of criminal liability